Estilo de vida y prácticas de autocuidado en el usuario con diabetes mellitus Casagrande - Lino Capristan, Angelica Soledad (2016)
Quantitative, descriptive, correlational, cross-sectional research, which was conducted to determine the relationship between Lifestyle and selfcare practices for the prevention of chronic kidney disease in diabetes mellitus user that are handled by a specialized medical center Casa Grande. Theoretical concepts of Orem Self-Care (1990) Lifestyle and Hernandez et al was taken into account. (2009). The population consisted of 95 members, determining a sample of 43 users, for calculating the sample size for finite population. The instruments used were: Questionnaire to assess the profile lifestyle and the Questionnaire for the assessment of user self-care practices with diabetes mellitus, both developed by the author. For data analysis the statistical test was applied chi square independence criteria (X2) in the SPPS version 21 program. Results found that 79% of users had an unhealthy lifestyle and 21% style healthy living; 77% had good self-care practices, followed by .23%; not finding any user with bad self-care practices. When the test statistic is found that there is no significant relationship between lifestyle and selfcare practices for the prevention of chronic kidney disease in diabetes mellitus user. (P-value> 0.05).